Bio-based acrylic pressure-sensitive adhesive and preparation method thereof

By using nanosilver modified spider silk nanofibers and jenipine as crosslinking agents in bio-based acrylic pressure-sensitive adhesives, the shortcomings of existing bio-based acrylic pressure-sensitive adhesives in terms of adhesion, weather resistance and antibacterial and mildew resistance are solved, and higher cohesion, tensile strength and antibacterial properties are achieved, and the service life is extended.

CN119662160AActive Publication Date: 2025-03-21PINGXIANGGAOHENG INNOTACK INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411959536.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing bio-based acrylic pressure-sensitive adhesives have shortcomings in adhesion, weather resistance and antibacterial and mildew resistance, resulting in a short service life.

Method used

Nanosilver modified spider silk nanofibers and jenipine are used as crosslinking agents, combining bio-based soft monomers, hard monomers and functional monomers to form a crosslinking network through specific preparation methods to improve the cohesion and antibacterial properties of the pressure-sensitive adhesive.

Benefits of technology

It significantly improves the cohesion, tensile strength and weather resistance of pressure-sensitive adhesives, extends their service life, and gives them good antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662160A_ABST
    Figure CN119662160A_ABST
Patent Text Reader

Abstract

The invention discloses a bio-based acrylic pressure-sensitive adhesive and a preparation method thereof, and belongs to the technical field of pressure-sensitive adhesives, the acrylic pressure-sensitive adhesive comprises, by weight, 45-90 parts of a bio-based soft monomer, 15-35 parts of a bio-based hard monomer, 10-20 parts of a bio-based functional monomer, 5-15 parts of modified bio-based nanofibers, 3-6 parts of a natural cross-linking agent, 80-150 parts of a solvent and 0.05-1 part of an initiator; wherein the modified bio-based nano-fibers are natural spider silk nano-fibers modified by nano-silver; the natural cross-linking agent is an iridoid compound. The modified spider silk nanofibers can improve the strength and toughness of the acrylic pressure-sensitive adhesive and enhance the cohesion strength of the pressure-sensitive adhesive, so that the peel strength is improved; the iridoid compound can form a three-dimensional network structure with the bio-based functional monomer through chemical reaction, so that the holding power is improved; by adding the nano-silver, the antibacterial ability of the pressure-sensitive adhesive is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressure-sensitive adhesives, and in particular relates to a bio-based acrylic pressure-sensitive adhesive and a preparation method thereof. Background Art

[0002] Pressure-sensitive adhesives, also known as pressure-sensitive adhesives (PSA), are a type of polymer material with long-term bonding properties. This material can quickly form a stable bond with the substrate by applying a slight pressure without heating, solvents, or chemical reactions. Since pressure-sensitive adhesives are easy to bond, easy to peel off, can be bonded repeatedly, and can be used stably in conventional or even harsh environments, PSA is widely used in daily necessities, electronics, construction, chemicals, medicine, automobiles, and aerospace industries.

[0003] At present, in addition to rubber pressure-sensitive adhesive and silicone rubber-based pressure-sensitive adhesive, acrylic pressure-sensitive adhesive is the most commonly used type. Acrylic pressure-sensitive adhesive is often prepared with petroleum-based monomers. However, with the acceleration of the industrialization process, human demand for petroleum, an important resource, is also rising. Petroleum is not only an indispensable source of fuel in daily life, but also the basis of many key industries such as chemical industry and transportation. However, in recent decades, it has become an indisputable fact that global oil resources have been gradually depleted, which not only limits the supply of oil, but also pushes up its market price. Affected by the fluctuation of oil prices, the price of acrylic pressure-sensitive adhesives prepared by petrochemical products has also increased accordingly. In addition, acrylic compounds synthesized from petroleum monomers are often difficult to degrade and cause great pollution to the environment. From a long-term development perspective, new materials with sustainable development have more development prospects.

[0004] Biomass resources are becoming an important raw material for obtaining clean energy and high-value chemicals due to their abundant reserves and renewable characteristics, and have received more and more attention. At present, researchers have begun to explore methods for preparing pressure-sensitive adhesives using biomass resources, aiming to develop new materials that are more environmentally friendly and sustainable. This research direction not only helps to reduce dependence on traditional petrochemical resources, but also provides new development opportunities for the pressure-sensitive adhesive industry. For example, the Chinese patent with authorization announcement number CN115785862B discloses a bio-based anti-warping acrylic pressure-sensitive adhesive and a preparation method thereof. The invention uses acrylic acid and polyfarnesylene glycol as bio-based functional monomers to prepare bio-based acrylic resins. Polyfarnesylene glycol contains double bonds and -OH, which can be used for free radical polymerization and cross-linking with curing agents to form a network structure to ensure the cohesive strength and anti-warping properties of the pressure-sensitive adhesive. Another example is the Chinese patent application with publication number CN111621241A, which discloses a method for preparing a biodegradable bio-based acrylic pressure-sensitive adhesive protective film. The main components of the bio-based (meth) acrylic ester monomer in the invention are derived from pine resin and natural plant oils, and the bio-based carbon content is not less than 70%. The raw materials used in the invention are easy to degrade and are green and environmentally friendly. However, compared with acrylic pressure-sensitive adhesives prepared from petroleum-based monomers, bio-based acrylic pressure-sensitive adhesives still have problems such as poor adhesion, poor weather resistance, and poor antibacterial and mildew resistance, which shortens the service life of bio-based acrylic pressure-sensitive adhesives. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a bio-based acrylic pressure-sensitive adhesive and a preparation method thereof. The bio-based acrylic pressure-sensitive adhesive not only uses bio-based raw materials instead of petroleum-based raw materials, but also has a simple preparation method and is easy to operate.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A bio-based acrylic pressure-sensitive adhesive, comprising, by weight, 45 to 90 parts of a bio-based soft monomer, 15 to 35 parts of a bio-based hard monomer, 10 to 20 parts of a bio-based functional monomer, 5 to 15 parts of modified bio-based nanofibers, 3 to 6 parts of a natural cross-linking agent, 80 to 150 parts of a solvent and 0.05 to 1 part of an initiator;

[0008] Wherein, the modified bio-based nanofiber is spider silk nanofiber modified by nanosilver; and the natural cross-linking agent is a cyclopentadiene ether terpene compound.

[0009] The present invention uses bio-based soft monomers, bio-based hard monomers and bio-based functional monomers as main components of the bio-based acrylic pressure-sensitive adhesive. The bio-based soft monomers are selected from acrylate monomers with longer side chains. The long side chains increase the flexibility of the polymer and reduce the glass transition temperature (Tg) of the polymer, so that the adhesive can still maintain good adhesion performance at a lower temperature; the bio-based hard monomers are selected from acrylate or methacrylate monomers with shorter side chains or no side chains. The addition of the hard monomers can significantly improve the cohesion of the pressure-sensitive adhesive, making it less likely to cause cohesive failure under high temperature conditions, and the short side chain or no side chain structure of the hard monomers improves the rigidity of the polymer; the bio-based functional monomers contain double bonds and carboxyl groups, so that they can react better with the cross-linking agent.

[0010] Preferably, the bio-based soft monomer is any one of 2-ethylhexyl acrylate, 2-octyl acrylate, and n-butyl acrylate; the bio-based hard monomer is selected from isobornyl methacrylate or methyl acrylate; and the bio-based functional monomer is acrylic acid.

[0011] Preferably, the iridoid compound is genipin; the solvent is any one of dimethyl sulfoxide, ethyl acetate, and isopropanol; and the initiator is azobisisobutyronitrile or benzoyl peroxide.

[0012] Spider silk, or spider silk for short, is known for its amazing strength and elasticity, and is known as "biological steel". Spider silk is very strong yet extremely light, making it of great application value in aviation, military equipment, and personal protection. Spider silk is mostly golden, transparent, smooth and shiny, with a physical density of about 1.13 to 1.29 g / cm 3, large breaking energy, strong UV resistance, not only high temperature resistance but also low temperature resistance. Thermal analysis by researchers shows that spider silk of the genus Nephila has good thermal stability below 200°C, hardens above 300°C, remains elastic at minus 40°C, and becomes brittle only at extremely low temperatures. As a natural product, spider silk can be completely biodegraded, which is very consistent with the current concept of green environmental protection. The main components of spider silk are composed of a series of different types of proteins, collectively known as spidroins. Spider silk protein is mainly composed of amino acids such as glycine (Gly), alanine (Al a), serine (Ser) and proline (Pro). It contains highly repetitive amino acid sequences, which are usually composed of β-folds composed of alanine and A-helical units rich in proline. These repetitive sequences make spider silk protein highly elastic and strong. At present, recombinant spider silk can also be obtained using genetic recombination technology, but its mechanical properties cannot be compared with natural spider silk. The spider silk used in the present invention is selected from the golden-spinning spider, which belongs to the family of the Arachnididae and has a large body. The female spider has a body length of 35 to 50 mm and a large web with a diameter of more than 1 meter. The excellent mechanical properties of the spider silk itself can enhance the tear resistance of the pressure-sensitive adhesive, making it difficult to break when subjected to external forces.

[0013] Nanosilver has excellent spectral antibacterial properties and can effectively inhibit the reproduction of a variety of bacteria, fungi and viruses. Spider silk is modified with nanosilver, and the modified solution is used to make a nanofiber membrane through electrospinning technology, so that nanosilver is filled into the tiny gaps of spider silk nanofibers, enhancing the overall density of the nanofibers and further improving the strength and wear resistance of spider silk nanofibers. The modified spider silk nanofibers can not only significantly improve the cohesive strength of the pressure-sensitive adhesive after modification, but also make the pressure-sensitive adhesive have good antibacterial properties, thereby extending the service life.

[0014] Genipin, or 5-hydroxy-1,4-naphthoquinone-2-β-D-glucoside, is a natural compound extracted from Gardenia fruit and belongs to the class of cyclopentadiene compounds. Genipin, which contains multiple hydroxyl groups, has a wide range of biological activities and can be used as an excellent natural cross-linking agent. It can be cross-linked with materials such as proteins, gelatin, and chitosan and used as a biomaterial in the fields of medical care and health. In the present invention, genipin is used as a cross-linking agent for acrylic pressure-sensitive adhesives. The hydroxyl groups in genipin can react with the carboxyl groups in bio-based acrylic functional monomers to form ester bonds, thereby forming a dense cross-linked network in the pressure-sensitive adhesive, which enhances the internal bonding tightness and improves the cohesion. The brief reaction equation involved is shown below:

[0015]

[0016] As a general technical concept, the present invention also provides a method for preparing a bio-based acrylic pressure-sensitive adhesive, such asFigure 1 As shown, the following steps are included:

[0017] Step (1), adding a bio-based soft monomer, a bio-based hard monomer, a bio-based functional monomer and a first part of an initiator into a reactor containing a first part of a solvent, wherein the first part of the solvent accounts for 50-70% of the total amount of the solvent, and the first part of the initiator accounts for 35-65% of the total amount of the initiator, heating and stirring for 10-30 minutes, condensing, and then refluxing and keeping warm to obtain a solution A;

[0018] Step (2), adding genipin and modified natural spider silk nanofibers to the remaining solvent, and ultrasonically stirring to obtain solution B;

[0019] Step (3), when the temperature of solution A in step (1) drops to a set temperature, solution B prepared in step (2) is added to solution A, stirred evenly, and the remaining initiator is added, the temperature is raised to react, and then refluxed to keep warm. After the reaction is completed, the solution is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0020] Preferably, in step (1), the heating temperature is 68 to 94° C., and the reflux insulation time is 3 to 8 hours.

[0021] Preferably, in step (2), ultrasonic stirring is performed 3 times, each time for 10 to 20 minutes; in step (3), solution A is cooled to 50°C, heated to 60 to 75°C, and refluxed for 1 to 5 hours. Ultrasonic stirring allows the modified spider silk nanofibers to be evenly dispersed in the pressure-sensitive adhesive.

[0022] Preferably, the preparation method of the modified natural spider silk nanofiber comprises the following steps:

[0023] Step (1), washing the natural spider silk with deionized water to remove excess impurities, drying, cutting into pieces and placing into a reactor containing 10 to 30 mL of a fluorinated solvent, stirring at room temperature until the spider silk is completely dissolved, and filtering to obtain a natural spider silk protein solution after the dissolution is complete;

[0024] Step (2), adding silver nitrate solution to step (1), stirring, and obtaining a natural spider silk protein solution modified with nano-silver;

[0025] Step (3), injecting the nanosilver-modified natural spider silk protein solution obtained in step (2) into an electrospinning apparatus, starting electrospinning, and obtaining nanosilver-modified natural spider silk nanofibers.

[0026] Preferably, in step (1), the drying temperature is 40-60°C, the drying time is 3-8 hours, the fluorinated solvent is hexafluoroisopropanol, and the stirring time is 6-10 hours. Hexafluoroisopropanol (HFIP) is a polar organic solvent with strong dissolving ability. Spider silk is a natural fiber composed of protein. This type of protein contains a large number of hydrogen bonds and other non-covalent interactions. HFIP can interrupt the hydrogen bond network inside the spider silk protein and dissolve the spider silk well.

[0027] Preferably, in step (2), the amount of silver nitrate used is 4 to 8% of the mass of natural spider silk, and the stirring time is 1 to 4 hours.

[0028] Preferably, in step (3), the parameters of electrospinning are: voltage 12-20 kV, receiving distance 6-18 cm, injection speed 40-80 μL / min.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The spider silk nanofibers modified with nanosilver are added in the present invention. The tightly stacked secondary structure of the spider silk protein contained in the spider silk makes it a semi-crystalline molecular spring structure, which determines that it has extremely high tensile strength and elastic modulus, so that the spider silk nanofibers play the role of skeleton support in the bio-based pressure-sensitive adhesive, greatly improving the cohesion and tensile strength of the pressure-sensitive adhesive, thereby improving the peel strength. In addition, the spider silk itself has the characteristics of UV resistance and high and low temperature resistance, which gives the pressure-sensitive adhesive good weather resistance; nanosilver itself has a broad spectrum of antibacterial activity, which can efficiently and quickly inhibit or kill various bacteria, fungi and viruses, which makes the prepared pressure-sensitive adhesive have good antibacterial properties. When nanosilver is used to modify spider silk nanofibers, the intermolecular heterogeneity between nanosilver and spider silk nanofibers can effectively avoid the agglomeration of spider silk fibers, making the spider silk nanofibers more evenly dispersed in the acrylic pressure-sensitive adhesive, maintaining the consistency of the entire system; at the same time, due to the high specific surface area characteristics brought by the size effect of nanosilver, it can be filled into the tiny gaps or defective areas inside the spider silk nanofibers. The two are coupled with each other, increasing the overall density of the spider silk nanofibers, and when subjected to external forces, nanosilver as a "filler" can offset part of the stress, thereby improving the overall strength and fracture resistance of the spider silk nanofibers, and then strengthening the cohesion of the pressure-sensitive adhesive, making it less likely to peel off.

[0031] (2) Genipin is added as a natural cross-linking agent in the present invention, and the genipin molecules can undergo a cross-linking reaction with acrylic acid to form a stable covalent bond, forming a compact three-dimensional cross-linking network, further improving the cross-linking density of the pressure-sensitive adhesive and increasing the viscosity of the pressure-sensitive adhesive. Moreover, as a natural compound, genipin itself also has certain antioxidant properties, can scavenge free radicals, help delay the aging of the pressure-sensitive adhesive, and maintain its long-term functional stability.

[0032] (3) The components used in the present invention use bio-based raw materials instead of petroleum raw materials, which is economical and environmentally friendly, reduces the risk of environmental pollution, conforms to the development trend of green chemistry, and is more conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flow chart of preparing bio-based acrylic pressure-sensitive adhesive. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described in detail below, and the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention. The present invention is further described below in conjunction with specific embodiments.

[0035] Unless otherwise specified in the examples of the present invention, the various components and chemical reagents used were obtained through conventional commercial channels:

[0036] 2-Ethylhexyl acrylate, 2-octyl acrylate, and n-butyl acrylate were purchased from Tesco Chemical (Hubei) Co., Ltd.

[0037] Isobornyl methacrylate and methyl acrylate were from Sigma-Aldrich (Shanghai) Biotechnology Co., Ltd.

[0038] Acrylic acid was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0039] Dimethyl sulfoxide, ethyl acetate, and isopropanol were purchased from Sinopharm Group.

[0040] Spider silk comes from Hainan Spider King Biotechnology Co., Ltd.

[0041] Genipin comes from Shaanxi Saien Biotechnology Co., Ltd.

[0042] Example 1

[0043] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 90 parts of 2-octyl acrylate, 30 parts of isobornyl methacrylate, 10 parts of acrylic acid, 5 parts of nano-silver modified spider silk nanofibers, 6 parts of genipin, 150 parts of dimethyl sulfoxide and 0.06 parts of azobisisobutyronitrile. The specific preparation process includes the following steps:

[0044] (1) Take fresh spider silk and wash it with deionized water to remove excess impurities. Place the washed spider silk in an oven at 50°C and dry it for 5 hours. After drying, cut it into pieces and place it in a vial containing 20 mL of HFIP. Stir it with a magnetic stirrer for 8 hours to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0045] (2) adding 0.03 parts of silver nitrate solution to step (1) and stirring for 3 hours to obtain a natural spider silk protein solution modified with nanosilver;

[0046] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 60 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 15 kV, and the distance from the needle to the receiver was 10 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0047] (4) Add 90 parts of dimethyl sulfoxide, 90 parts of 2-octyl acrylate, 30 parts of isobornyl methacrylate, 10 parts of acrylic acid and 0.03 parts of azobisisobutyronitrile into a four-necked bottle, slowly heat to 86° C. in a constant temperature water bath, stir for 20 minutes, and then condense. Reflux the system and keep it warm for 6 hours to obtain solution A;

[0048] (5) 6 parts of genipin and 5 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 60 parts of dimethyl sulfoxide, and ultrasonically stirred for 3 times, each time for 15 minutes, to obtain a solution B;

[0049] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.03 parts of azobisisobutyronitrile is added thereto, and the temperature is raised to 65° C., followed by reflux and heat preservation for 3 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0050] Example 2

[0051] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 60 parts of 2-octyl acrylate, 22 parts of methyl acrylate, 15 parts of acrylic acid, 10 parts of nano-silver modified spider silk nanofibers, 3 parts of genipin, 100 parts of ethyl acetate and 1 part of azobisisobutyronitrile. The specific preparation process includes the following steps:

[0052] (1) Take fresh spider silk and wash it with deionized water to remove excess impurities. Place the washed spider silk in an oven at 40°C and dry it for 3 hours. After drying, cut it into pieces and place it in a vial containing 30 mL of HFIP. Stir it with a magnetic stirrer for 10 hours to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0053] (2) adding 0.4 parts of silver nitrate solution to step (1) and stirring for 1 hour to obtain a natural spider silk protein solution modified with nanosilver;

[0054] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 40 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 12 kV, and the distance from the needle to the receiver was 6 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0055] (4) Add 50 parts of ethyl acetate, 60 parts of 2-octyl acrylate, 22 parts of methyl acrylate, 15 parts of acrylic acid and 0.65 parts of azobisisobutyronitrile into a four-necked bottle, slowly heat to 88° C. in a constant temperature water bath, stir for 15 minutes, and then condense. Reflux the system and keep it warm for 8 hours to obtain solution A;

[0056] (5) 3 parts of genipin and 10 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 50 parts of ethyl acetate, and ultrasonically stirred for 3 times, each time for 10 minutes, to obtain a solution B;

[0057] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.35 parts of azobisisobutyronitrile is added thereto, and the temperature is raised to 60° C., followed by reflux and heat preservation for 5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0058] Example 3

[0059] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 45 parts of 2-octyl acrylate, 15 parts of isobornyl methacrylate, 12 parts of acrylic acid, 15 parts of nano-silver modified spider silk nanofibers, 4 parts of genipin, 80 parts of isopropanol and 0.05 parts of benzoyl peroxide. The specific preparation process includes the following steps:

[0060] (1) Take fresh spider silk and wash it with deionized water to remove excess impurities. Place the washed spider silk in an oven at 60°C and dry it for 8 hours. After drying, cut it into pieces and place it in a vial containing 10 mL of HFIP. Stir it with a magnetic stirrer for 6 hours to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0061] (2) adding 0.75 parts of silver nitrate solution to step (1) and stirring for 4 hours to obtain a natural spider silk protein solution modified with nanosilver;

[0062] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 80 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 20 kV, and the distance from the needle to the receiver was 18 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0063] (4) Add 56 parts of isopropanol, 45 parts of 2-octyl acrylate, 15 parts of isobornyl methacrylate, 12 parts of acrylic acid and 0.00175 parts of benzoyl peroxide into a four-necked bottle, slowly heat to 68° C. in a constant temperature water bath, stir for 30 minutes, and then condense. Reflux the system and keep it warm for 3 hours to obtain solution A;

[0064] (5) 4 parts of genipin and 15 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 24 parts of isopropanol, and ultrasonically stirred for 3 times, each time for 20 minutes, to obtain a solution B;

[0065] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.04825 parts of benzoyl peroxide is added thereto, and the temperature is raised to 75° C., followed by reflux and heat preservation for 2 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0066] Example 4

[0067] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 80 parts of 2-ethylhexyl acrylate, 25 parts of isobornyl methacrylate, 20 parts of acrylic acid, 7 parts of nano-silver modified spider silk nanofibers, 5 parts of genipin, 120 parts of dimethyl sulfoxide and 0.09 parts of azobisisobutyronitrile. The specific preparation process includes the following steps:

[0068] (1) Wash fresh spider silk with deionized water to remove excess impurities, place the washed spider silk in an oven at 45°C to dry for 4 hours, cut it into pieces after drying and place it in a vial containing 15 mL of HFIP, stir it with a magnetic stirrer for 7 hours to dissolve it; filter the dissolved solution with a filter to obtain a natural spider silk protein solution;

[0069] (2) adding 0.42 parts of silver nitrate solution to step (1) and stirring for 3.5 hours to obtain a natural spider silk protein solution modified with nanosilver;

[0070] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 75 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 18 kV, and the distance from the needle to the receiver was 14 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0071] (4) Add 84 parts of dimethyl sulfoxide, 80 parts of 2-ethylhexyl acrylate, 25 parts of isobornyl methacrylate, 20 parts of acrylic acid and 0.036 parts of azobisisobutyronitrile into a four-necked bottle, slowly heat to 70° C. in a constant temperature water bath, stir for 20 minutes, and then condense. Reflux the system and keep it warm for 5 hours to obtain solution A;

[0072] (5) 5 parts of genipin and 7 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 36 parts of dimethyl sulfoxide, and ultrasonically stirred for 3 times, each time for 12 minutes, to obtain a solution B;

[0073] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.054 parts of azobisisobutyronitrile is added thereto, and the temperature is raised to 62° C., followed by reflux and heat preservation for 3 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0074] Example 5

[0075] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 75 parts of 2-ethylhexyl acrylate, 23 parts of methyl acrylate, 13 parts of acrylic acid, 8 parts of nano-silver modified spider silk nanofibers, 4 parts of genipin, 130 parts of ethyl acetate and 0.08 parts of azobisisobutyronitrile. The specific preparation process includes the following steps:

[0076] (1) Wash fresh spider silk with deionized water to remove excess impurities, place the washed spider silk in an oven at 55°C and dry for 5 h. After drying, cut it into pieces and place it in a vial containing 25 mL of HFIP. Stir it with a magnetic stirrer for 6.5 h to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0077] (2) adding 0.4 parts of silver nitrate solution to step (1) and stirring for 2.5 hours to obtain a natural spider silk protein solution modified with nanosilver;

[0078] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 45 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 14 kV, and the distance from the needle to the receiver was 12 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0079] (4) Add 71.5 parts of ethyl acetate, 75 parts of 2-ethylhexyl acrylate, 23 parts of methyl acrylate, 13 parts of acrylic acid and 0.032 parts of azobisisobutyronitrile into a four-necked bottle, slowly heat to 90° C. in a constant temperature water bath, stir for 12 minutes, and then condense. Reflux the system and keep it warm for 7 hours to obtain solution A;

[0080] (5) 4 parts of genipin and 8 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 58.5 parts of ethyl acetate, and ultrasonically stirred for 3 times, each time for 14 minutes, to obtain a solution B;

[0081] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.048 parts of azobisisobutyronitrile is added thereto, and the temperature is raised to 62° C., followed by reflux and heat preservation for 4.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0082] Example 6

[0083] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 50 parts of 2-ethylhexyl acrylate, 16 parts of isobornyl methacrylate, 14 parts of acrylic acid, 12 parts of nano-silver modified spider silk nanofibers, 3 parts of genipin, 90 parts of isopropanol and 0.5 parts of benzoyl peroxide. The specific preparation process includes the following steps:

[0084] (1) Wash fresh spider silk with deionized water to remove excess impurities, place the washed spider silk in an oven at 48°C and dry for 4.5 hours. After drying, cut it into pieces and place it in a vial containing 22 mL of HFIP. Stir it with a magnetic stirrer for 5.5 hours to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0085] (2) adding 0.84 parts of silver nitrate solution to step (1) and stirring for 1.5 hours to obtain a natural spider silk protein solution modified with nanosilver;

[0086] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 55 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 13 kV, and the distance from the needle to the receiver was 11 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0087] (4) Add 58.5 parts of isopropanol, 50 parts of 2-ethylhexyl acrylate, 16 parts of isobornyl methacrylate, 14 parts of acrylic acid and 0.3 parts of benzoyl peroxide into a four-necked bottle, slowly heat to 72° C. in a constant temperature water bath, stir for 25 minutes, and then condense. Reflux the system and keep it warm for 4.5 hours to obtain solution A;

[0088] (5) 3 parts of genipin and 12 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 31.5 parts of isopropanol, and ultrasonically stirred for 3 times, each time for 13 minutes, to obtain a solution B;

[0089] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.2 parts of benzoyl peroxide is added thereto, and the temperature is raised to 64° C., followed by reflux and heat preservation for 2.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0090] Example 7

[0091] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 65 parts of n-butyl acrylate, 21 parts of isobornyl methacrylate, 14 parts of acrylic acid, 9 parts of nano-silver modified spider silk nanofibers, 6 parts of genipin, 110 parts of dimethyl sulfoxide and 0.4 parts of azobisisobutyronitrile. The specific preparation process includes the following steps:

[0092] (1) Wash fresh spider silk with deionized water to remove excess impurities, place the washed spider silk in an oven at 46°C and dry for 7.5 hours. After drying, cut it into pieces and place it in a vial containing 18 mL of HFIP. Stir it with a magnetic stirrer for 8.5 hours to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0093] (2) adding 0.45 parts of silver nitrate solution to step (1), stirring for 2.5 hours, and obtaining a natural spider silk protein solution modified with nanosilver;

[0094] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 63 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 16 kV, and the distance from the needle to the receiver was 13 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0095] (4) Add 72.6 parts of dimethyl sulfoxide, 65 parts of n-butyl acrylate, 21 parts of isobornyl methacrylate, 14 parts of acrylic acid and 0.16 parts of azobisisobutyronitrile into a four-necked bottle, slowly heat to 77° C. in a constant temperature water bath, stir for 20 minutes, and then condense. Reflux the system and keep it warm for 5.5 hours to obtain solution A;

[0096] (5) 6 parts of genipin and 9 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 37.4 parts of dimethyl sulfoxide, and ultrasonically stirred for 3 times, each time for 11 minutes, to obtain a solution B;

[0097] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.24 parts of azobisisobutyronitrile is added thereto, and the temperature is raised to 73° C., followed by reflux and heat preservation for 3.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0098] Example 8

[0099] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 76 parts of n-butyl acrylate, 23 parts of methyl acrylate, 11 parts of acrylic acid, 6 parts of nano-silver modified spider silk nanofibers, 5 parts of genipin, 140 parts of ethyl acetate and 0.1 parts of azobisisobutyronitrile. The specific preparation process includes the following steps:

[0100] (1) Wash fresh spider silk with deionized water to remove excess impurities, place the washed spider silk in an oven at 44°C and dry for 6 h. After drying, cut it into pieces and place it in a vial containing 16 mL of HFIP. Stir it with a magnetic stirrer for 9 h to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0101] (2) adding 0.33 parts of silver nitrate solution to step (1) and stirring for 3 hours to obtain a natural spider silk protein solution modified with nanosilver;

[0102] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 74 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 17 kV, and the distance from the needle to the receiver was 8 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0103] (4) Add 67.2 parts of ethyl acetate, 76 parts of n-butyl acrylate, 23 parts of methyl acrylate, 11 parts of acrylic acid and 0.04 parts of azobisisobutyronitrile into a four-necked flask, slowly heat to 92° C. in a constant temperature water bath, stir for 18 minutes, and then condense. Reflux the system and keep it warm for 7.5 hours to obtain solution A;

[0104] (5) 5 parts of genipin and 8 parts of the nanosilver-modified spider silk nanofibers prepared in step (3) were placed in a conical flask containing 72.8 parts of ethyl acetate, and ultrasonically stirred for 3 times, each time for 16 min, to obtain a solution B;

[0105] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.06 parts of azobisisobutyronitrile is added thereto, and the temperature is raised to 66° C., followed by reflux and heat preservation for 4.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0106] Example 9

[0107] A bio-based acrylic pressure-sensitive adhesive is prepared from the following raw materials in parts by weight: 85 parts of n-butyl acrylate, 27 parts of isobornyl methacrylate, 14 parts of acrylic acid, 13 parts of nano-silver modified spider silk nanofibers, 4 parts of genipin, 135 parts of isopropanol and 0.07 parts of benzoyl peroxide. The specific preparation process includes the following steps:

[0108] (1) Wash fresh spider silk with deionized water to remove excess impurities, place the washed spider silk in an oven at 42°C and dry for 7.5 hours. After drying, cut it into pieces and place it in a vial containing 12 mL of HFIP. Stir it with a magnetic stirrer for 9.5 hours to dissolve it. Filter the dissolved solution with a filter to obtain a natural spider silk protein solution.

[0109] (2) adding 0.728 parts of silver nitrate solution to step (1) and stirring for 4 hours to obtain a natural spider silk protein solution modified with nanosilver;

[0110] (3) placing the nanosilver-modified natural spider silk protein solution obtained in step (2) into an injection syringe, and extruding it at a rate of 55 μL / min through a microinjection pump. During the spinning process, the voltage was controlled to be 15 kV, and the distance from the needle to the receiver was 9 cm, thereby obtaining nanosilver-modified natural spider silk nanofibers;

[0111] (4) Add 86.4 parts of isopropanol, 85 parts of n-butyl acrylate, 27 parts of isobornyl methacrylate, 14 parts of acrylic acid and 0.0364 parts of benzoyl peroxide into a four-necked bottle, slowly heat to 74° C. in a constant temperature water bath, stir for 24 minutes, and then condense. Reflux the system and keep it warm for 4.5 hours to obtain solution A;

[0112] (5) 4 parts of genipin and 13 parts of the natural spider silk nanofibers modified with nanosilver prepared in step (3) were placed in a conical flask containing 48.6 parts of isopropanol, and ultrasonically stirred for 3 times, each time for 18 minutes, to obtain a solution B;

[0113] (6) After solution A is cooled to 50° C., solution B obtained in step (5) is added thereto, and the remaining 0.04336 parts of benzoyl peroxide is added thereto, and the temperature is raised to 68° C., followed by reflux and heat preservation for 2.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

[0114] Comparative Example 1

[0115] A bio-based acrylic pressure-sensitive adhesive is the same as Example 1 except that it does not contain natural spider silk nanofibers modified with nano-silver.

[0116] Comparative Example 2

[0117] A bio-based acrylic pressure-sensitive adhesive is the same as Example 1 except that it does not contain genipin.

[0118] Comparative Example 3

[0119] A bio-based acrylic pressure-sensitive adhesive is the same as Example 1 except that it does not contain nano-silver.

[0120] The products prepared in Examples 1-9 and the bio-based pressure-sensitive adhesive prepared in Comparative Examples 1-3 were coated on a PE T base film with a thickness of 80 μm, dried at 120° C. for 3 min to obtain a pressure-sensitive adhesive tape with a dry adhesive thickness of 50 μm, and cured by UV curing machine for 40 seconds, and its performance was tested.

[0121] First, the adhesion and durability of the pressure-sensitive tape were tested, with reference to the standards GB / T 2792-2014 for testing its 180° peel strength and GB / T 4851-2017 for testing its initial adhesion. The specific results of the test are shown in Table 1.

[0122] Table 1 Viscosity and durability test results of Examples 1 to 9 and Comparative Examples 1 to 3

[0123]

[0124]

[0125] 180° peel force (N / 25mm) and persistent adhesion at 20°C are important parameters for evaluating the adhesion and durability of pressure-sensitive adhesives. 180° peel force refers to the force required to peel the pressure-sensitive adhesive from the substrate at an angle of 180°, reflecting the adhesion strength between the pressure-sensitive adhesive and the substrate. A higher peel force means a stronger adhesion. Persistent adhesion refers to the ability of a pressure-sensitive adhesive to maintain adhesion under specific temperature and time conditions. It is usually tested under standard conditions of 20°C to evaluate its long-lasting adhesion at room temperature. As can be seen from Table 1, Examples 1 to 9 provided by the present invention have high peel strength and good long-lasting adhesion performance. The persistent adhesion at 20°C can last for more than 72 hours without displacement, which can ensure its long-term working performance. Compared with Examples 1 to 9, Comparative Example 1 does not contain natural spider silk nanofibers modified with nanosilver, and its 180° peel force is only 6.3N / 25mm, which is smaller than the minimum 11.7N / 25mm in the embodiment, and the adhesion at 20°C is much less than 72h, indicating that the addition of modified natural spider silk nanofibers can effectively enhance the adhesion and durability of the pressure-sensitive adhesive; similarly, Comparative Example 2 does not contain genipin, and its 180° peel force is only 67.2N / 25mm, which is higher than Comparative Example 1, but still less than 11.7N / 25mm, and the adhesion at 20°C is much less than 72h, indicating that genipin can also improve the adhesion and service life of the pressure-sensitive adhesive.

[0126] Subsequently, the antibacterial properties of the pressure-sensitive adhesive were tested, and the test bacteria were Escherichia coli and Staphylococcus aureus. Referring to GB / T20944-2007, the pressure-sensitive adhesives prepared in Examples 1 to 9 and Comparative Examples 1 to 3 were immersed in water for 72 hours, and then their antibacterial properties were tested. The specific results are shown in Table 2.

[0127] Table 2 Antibacterial performance test results of Examples 1 to 9 and Comparative Examples 1 to 3

[0128]

[0129]

[0130] It can be seen from Table 2 that the pressure-sensitive adhesives prepared in Examples 1 to 9 provided by the present invention have good antibacterial properties, and the antibacterial rates against Escherichia coli and Staphylococcus aureus can reach more than 98%. After soaking in water for 72 hours, the antibacterial rates against Escherichia coli and Staphylococcus aureus can still be maintained at more than 96.5%, indicating that the pressure-sensitive adhesive prepared by the present invention has good and lasting antibacterial effects. The pressure-sensitive adhesive without nanosilver in Comparative Example 3 has significantly lower initial antibacterial properties and antibacterial properties after soaking in water for 72 hours than Examples 1 to 9, indicating that nanosilver helps to improve the antibacterial properties of the pressure-sensitive adhesive.

[0131] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A bio-based acrylic pressure-sensitive adhesive, characterized in that: The acrylic pressure-sensitive adhesive comprises, by weight, 45 to 90 parts of a bio-based soft monomer, 15 to 35 parts of a bio-based hard monomer, 10 to 20 parts of a bio-based functional monomer, 5 to 15 parts of modified bio-based nanofibers, 3 to 6 parts of a natural cross-linking agent, 80 to 150 parts of a solvent, and 0.05 to 1 part of an initiator; Wherein, the modified bio-based nanofiber is a natural spider silk nanofiber modified by nanosilver; and the natural cross-linking agent is an cyclopentadiene ether terpene compound.

2. A bio-based acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The bio-based soft monomer is any one of 2-ethylhexyl acrylate, 2-octyl acrylate, and n-butyl acrylate; the bio-based hard monomer is selected from isobornyl methacrylate or methyl acrylate; and the bio-based functional monomer is acrylic acid.

3. The bio-based acrylic pressure-sensitive adhesive according to claim 1, characterized in that: The iridoid compound is genipin; the solvent is selected from any one of dimethyl sulfoxide, ethyl acetate and isopropanol; and the initiator is azobisisobutyronitrile or benzoyl peroxide.

4. A method for preparing a bio-based acrylic pressure-sensitive adhesive according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step (1), adding a bio-based soft monomer, a bio-based hard monomer, a bio-based functional monomer and a first part of an initiator into a reactor containing a first part of a solvent, wherein the first part of the solvent accounts for 50-70% of the total amount of the solvent, and the first part of the initiator accounts for 35-65% of the total amount of the initiator, heating and stirring for 10-30 minutes, condensing, and then refluxing and keeping warm to obtain a solution A; Step (2), adding genipin and modified natural spider silk nanofibers to the remaining solvent, and ultrasonically stirring to obtain solution B; Step (3), when the temperature of solution A in step (1) drops to a set temperature, solution B prepared in step (2) is added to solution A, stirred evenly, and the remaining initiator is added, the temperature is raised to react, and then refluxed to keep warm. After the reaction is completed, the solution is cooled to room temperature to obtain a bio-based acrylic pressure-sensitive adhesive.

5. The method for preparing a bio-based acrylic pressure-sensitive adhesive according to claim 4, characterized in that: In the step (1), the heating temperature is 68 to 94° C., and the reflux insulation time is 3 to 8 hours.

6. The method for preparing a bio-based acrylic pressure-sensitive adhesive according to claim 4, characterized in that: In the step (2), ultrasonic stirring is performed three times, each time for 10 to 20 minutes; in the step (3), the temperature of solution A is reduced to 50° C., then raised to 60 to 75° C., and refluxed for 1 to 5 hours.

7. The method for preparing a bio-based acrylic pressure-sensitive adhesive according to claim 4, characterized in that: The preparation method of the modified natural spider silk nanofiber comprises the following steps: Step (1), washing the natural spider silk with deionized water, drying it, cutting it into pieces and placing it in a reactor containing a fluorinated solvent, stirring it at room temperature until the spider silk is completely dissolved, and filtering it after the dissolution is complete to obtain a natural spider silk protein solution; Step (2), adding silver nitrate solution to step (1), stirring, and obtaining a natural spider silk protein solution modified with nano-silver; Step (3), injecting the nanosilver-modified natural spider silk protein solution obtained in step (2) into an electrospinning apparatus, starting electrospinning, and obtaining nanosilver-modified natural spider silk nanofibers.

8. The method for preparing a bio-based acrylic pressure-sensitive adhesive according to claim 7, characterized in that: In the step (1), the drying temperature is 40-60° C., and the drying time is 3-8 hours; the fluorinated solvent is hexafluoroisopropanol, the amount used is 10-30 mL, and the stirring time is 6-10 hours.

9. The method for preparing a bio-based acrylic pressure-sensitive adhesive according to claim 7, characterized in that: In the step (2), the amount of silver nitrate used is 4 to 8% of the mass of the natural spider silk, and the stirring time is 1 to 4 hours.

10. The method for preparing a bio-based acrylic pressure-sensitive adhesive according to claim 7, characterized in that: In the step (3), the parameters of electrospinning are: voltage 12-20 kV, receiving distance 6-18 cm, injection speed 40-80 μL / min.

Citation Information

Patent Citations

  • Preparation method of degradable bio-based acrylate pressure-sensitive adhesive protective film

    CN111621241A

  • A bio-based anti-warping acrylic pressure-sensitive adhesive and its preparation method

    CN115785862B

  • Preparation method of medical adhesive

    CN108359406A

  • Bio-based acrylate pressure-sensitive adhesive and preparation method thereof

    CN117777902A

  • Binder, preparation method thereof and battery

    CN118099432A